Narrative Restrictions and Proxies: Rejoinder. Issue 4 (2nd October 2022) - Giacomini, Raffaella; Kitagawa, Toru; Read, Matthew
Abstract : This rejoinder addresses the discussants' specific comments on the article "Narrative Restrictions and Proxies" (Section 2) as well as more general comments on the approach to robust Bayesian inference that we have proposed in previous work (Section 1).